2022
DOI: 10.1038/s41598-022-15759-6
|View full text |Cite
|
Sign up to set email alerts
|

Tibial sagittal and rotational alignment reduce patellofemoral stresses in posterior stabilized total knee arthroplasty

Abstract: Patellofemoral joint complications remain an important issue in total knee arthroplasty. We compared the patellofemoral contact status between cruciate-retaining and posterior-stabilized designs with varying degrees of tibial sagittal and rotational alignment using a computer simulation to ensure proper alignments in total knee arthroplasty. Knee kinematics, patellofemoral contact force and quadriceps force were computed using a musculoskeletal modeling program (LifeMOD/KneeSIM 2010; LifeModeler, Inc., San Cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The contemporary literature still lacks studies on modeling various pathological conditions of the knee joint capsuloligamentous apparatus work. The results of our experiment on the biomechanical model of the knee joint showed coincidence of patellar movements with clinical experience when its ligamentous apparatus is damaged [27][28][29][30][31]. In this paper, we presented results for passive knee joint fl exion modeling.…”
Section: Dicsussionmentioning
confidence: 73%
“…The contemporary literature still lacks studies on modeling various pathological conditions of the knee joint capsuloligamentous apparatus work. The results of our experiment on the biomechanical model of the knee joint showed coincidence of patellar movements with clinical experience when its ligamentous apparatus is damaged [27][28][29][30][31]. In this paper, we presented results for passive knee joint fl exion modeling.…”
Section: Dicsussionmentioning
confidence: 73%
“…In contrast, in the control group, the femoral components displayed external rotation, while the tibial components showed internal rotation. This can be explained by the effects of soft‐tissue laxity [ 6 , 13 , 23 , 40 ]. All the patients in the cohort were treated using the measured resection technique with mechanical alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ethical reason according to radiographic exposure, multiple bone models are currently unavailable. Changing the experimental conditions in a bone model, which was hard to be performed in the real world, is the strength of the computer simulation study, and numbers of studies have reported using single validated bone model 8 , 25 , 26 , 28 , 32 34 . However, there are anatomic variations depending on sex, race and individual even in healthy volunteer 35 .…”
Section: Discussionmentioning
confidence: 99%